Coral Reef Geometry and Hydrodynamics in Beach Erosion Control in North Quintana Roo, Mexico - Escudero, Mireille; Reguero, Borja G.; Mendoza, Edgar; Secaira, Fernando; Silva, Rodolfo (Frontiers in Marine Science, 2021)
Coral reefs are increasingly recognized for their shoreline protection services. The hydrodynamic performance of this ecosystem is comparable to artificial low-crested structures often used in coastal protection, whose objective is to emulate the former. Coral reefs also provide other important environmental services (e.g. food production, habitat provision, maintenance of biodiversity and social and cultural services) and leave almost no ecological footprint when conservation and restoration actions are conducted to maintain their coastal protection service. However, studies have focused on their flood protection service, but few have evaluated the morphological effects of coral reefs through their ability to avoid or mitigate coastal erosion. In this paper, we investigate the relation between shoreline change, reefs’ geometry and hydrodynamic parameters to elucidate the physics related to how the Mesoamerican Reef in Mexico protects sandy coastlines from erosion. Using numerical wave propagation and historical shoreline change calculated from satellite imagery, a direct correlation was found between shoreline movement, the depths and widths of reef flats, changes in the wave energy flux, and the radiation stresses of breaking waves. The findings indicate that the most remarkable efficacy in preventing beach erosion is due to reefs with shallow crests, wide reef flats, a dissipative lagoon seabed, located at 300 m from the coastline. The results provide essential insights for reef restoration projects focused on erosion mitigation and designing artificial reefs in microtidal sandy beaches. Results are limited to wave-dominated coasts.